Intestinal microbiota shifts by dietary intervention during extreme heat summer episodes in farmed gilthead sea bream (Sparus aurata) - R. Domingo-Bretón; S. Cools; F. Moroni; A. Belenguer; J.A. Calduch-Giner; E. Croes; P.G. Holhorea; F. Naya-Català; H. Boon; J. Pérez-Sánchez (Aquaculture Reports)
Climate change and its associated extreme events alter a number of physiological processes that also affect the homeostatic relationship of the host with their microbial communities. The aim of this study was to gain more insights on this issue, examining the effect of the record breaking-heat summer of 2022 on the gut microbiota of farmed gilthead sea bream (Sparus aurata), reared from May to August at the IATS research infrastructure (Spain´s Mediterranean coast). Fish were fed daily with four experimental diets, containing two different lipid levels (16 % and 14 %) with/without a commercial emulsifier (0.1 %; Volamel Aqua, Nukamel). On August 9th, concurrently with the historical record of water temperature (30.49 ºC), fish were sampled for analysis of blood-stress markers and water/intestinal microbiota. Gut microbiota analysis clearly evidenced the increased abundance of bacteria of Spirochaetota phylum, mainly represented by the genus Brevinema. This microbiota shift was not driven by environmental colonization as this bacteria genus remained residual in water samples with the increase of temperature. Bayesian network and functional enrichment analyses suggested that the high abundance of Brevinema exploits and negatively enhances a condition of imbalance in intestinal homeostasis, which was almost completely reversed by the use of dietary emulsifiers in combination with low energized diets. This phenotype restoration occurred in concomitance with changes in circulating levels of cortisol and glucose. Altogether this highlights the potential use of Brevinema as a heat-stress indicator, reinforcing the value of dietary intervention as a valuable solution to mitigate the negative impact of global warming on aquaculture production.